2016
DOI: 10.1113/jp272065
|View full text |Cite
|
Sign up to set email alerts
|

Systemic leukotriene B4 receptor antagonism lowers arterial blood pressure and improves autonomic function in the spontaneously hypertensive rat

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 87 publications
1
10
0
Order By: Relevance
“…Among the changes noted during this pre-hypertension period were dysregulation of pro-fibrotic pathways (e.g., upregulation of enolase-1) and inflammatory pathways (e.g., inhibition of interferons, TLR3 and STAT1) as well as altered mitochondrial function. The authors proposed that these changes support previously reported immune cell infiltration ( Waki et al, 2007 , 2013 ; Xu et al, 2012 ; Marvar et al, 2016 ). The resulting vessel remodeling alters vascular function, increasing cerebrovascular resistance and decreasing CBF, both of which contribute to increased sympathetic nerve activity via the Cushing mechanism, as recently reviewed ( McBryde et al, 2017 ).…”
Section: Vascular Risk Factors and The Nvusupporting
confidence: 76%
“…Among the changes noted during this pre-hypertension period were dysregulation of pro-fibrotic pathways (e.g., upregulation of enolase-1) and inflammatory pathways (e.g., inhibition of interferons, TLR3 and STAT1) as well as altered mitochondrial function. The authors proposed that these changes support previously reported immune cell infiltration ( Waki et al, 2007 , 2013 ; Xu et al, 2012 ; Marvar et al, 2016 ). The resulting vessel remodeling alters vascular function, increasing cerebrovascular resistance and decreasing CBF, both of which contribute to increased sympathetic nerve activity via the Cushing mechanism, as recently reviewed ( McBryde et al, 2017 ).…”
Section: Vascular Risk Factors and The Nvusupporting
confidence: 76%
“…) and, in experimental animal models of CV disease, anti‐inflammatory treatments have been shown to affect autonomic and baroreceptor function (Marvar et al . ). PTSD is associated with higher circulating levels of inflammatory markers (von Kanel et al .…”
Section: Discussionmentioning
confidence: 97%
“…Decreased BRS could be one contributing mechanisms underlying the link between PTSD and cardiovascular disease risk. Chronic inflammation may contribute to blunted BRS in PTSD because several studies have demonstrated that immune dysfunction is present in this population (von Kanel et al 2007;Spitzer et al 2010;Plantinga et al 2013) and, in experimental animal models of CV disease, anti-inflammatory treatments have been shown to affect autonomic and baroreceptor function (Marvar et al 2016). PTSD is associated with higher circulating levels of inflammatory markers (von Kanel et al 2007;Spitzer et al 2010;Plantinga et al 2013) including CRP, IL-4, IL-6 and intercellular adhesion molecule-1, higher brain angiotensin II levels (Matsumura et al 1998;Saavedra et al 2011), and greater arterial stiffness (Walczewska et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…), the baroreflex (Head & Adams, ; Marvar et al . ), the Bezold‐Jarish reflex (Widdop et al . ), and mechano‐ and metabo‐reflexes from skeletal muscle (Leal et al .…”
Section: Discussionmentioning
confidence: 99%